Muslim-Christian relations in Central Asia - Van Gorder, A. Christian. (Central Asian studies series., 2008)
This book explores issues of cultural tension that affect Muslim and Christian interaction within the Central Asian context. It looks at the ways that Christians have interacted with Central Asian Muslims in the past and discusses possible ways to improve Muslim-Christian relations in the present and future.